2003
DOI: 10.1242/dev.00719
|View full text |Cite
|
Sign up to set email alerts
|

Egfr/Ras pathway mediates interactions between peripodial and disc proper cells inDrosophilawing discs

Abstract: All imaginal discs in Drosophila are made up of a layer of columnar epithelium or the disc proper and a layer of squamous epithelium called the peripodial membrane. Although the developmental and molecular events in columnar epithelium or the disc proper are well understood, the peripodial membrane has gained attention only recently. Using the technique of lineage tracing, we show that peripodial and disc proper cells arise from a common set of precursors cells in the embryo, and that these cells diverge in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
66
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 53 publications
(69 citation statements)
references
References 47 publications
3
66
0
Order By: Relevance
“…Together the data support the idea that CG4382 functions as a negative regulator of vein development, which is repressed by a high level of Egfr signaling. The expression of CG4382 in the peripodial membrane overlying the disc proper suggests that its function in venation appears to involve communication between two cell layers, as has been noted for patterning of the major regions of the wing disc (Baena-Lopez et al 2003;Pallavi and Shashidhara 2003). Our results suggest the peripodial membrane may also have a more specific role in vein patterning.…”
Section: Cg6234supporting
confidence: 73%
“…Together the data support the idea that CG4382 functions as a negative regulator of vein development, which is repressed by a high level of Egfr signaling. The expression of CG4382 in the peripodial membrane overlying the disc proper suggests that its function in venation appears to involve communication between two cell layers, as has been noted for patterning of the major regions of the wing disc (Baena-Lopez et al 2003;Pallavi and Shashidhara 2003). Our results suggest the peripodial membrane may also have a more specific role in vein patterning.…”
Section: Cg6234supporting
confidence: 73%
“…To investigate how BM remodeling contributes to tissue development, we chose to inhibit MMP function by targeted overexpression of the Drosophila tissue inhibitor of metalloproteases (TIMP) (14) using the UAS/GAL4 system (15). Overexpression of TIMP in the larval fat body, driven by Lsp2-GAL4 (Lsp2ϾTIMP) (16) and in the peripodial epithelium of the larval wing imaginal discs, by Ubx-GAL4 (UbxϾTIMP) (17), resulted in striking phenotypes that we focused on for further characterization [ Fig. 1 and supporting information (SI) Fig.…”
Section: Reduction Of Mmp Activities Results In Disc Eversionmentioning
confidence: 99%
“…of EGFR/RAS pathway in the wing disc PM affects wingnotum/hinge decision in DP (Pallavi and Shashidhara, 2003). It has also been observed that puckered (puc), a negative regulator of the Jun N-terminal kinase (JNK) pathway, and hemipterous (hep), which encodes Drosophila JNK-kinase, are expressed in cells at the medial edge of the wing disc PM (Agnes et al, 1999).…”
mentioning
confidence: 99%